Analisis Faktor Yang Mempengaruhi Besarnya Profitabilitas Pada Bank Umum Syariah Di Indonesia Periode Januari 2017-Desember 2018 - Mukhamad Zakariya (JES (Jurnal Ekonomi Syariah), 2019)
The emergence of new Islamic banks creates healthy competition among Islamic banks both in terms of improving services, as well as improving the performance of the banks themselves. As one of the institutions that has an important role in the country's economy, banking regulators need to conduct controlled and comprehensive performance monitoring to improve the performance of Islamic banking so that the bank remains healthy and efficient. Profitability is the most important indicator to measure the performance of a bank. Return on assets (ROA) focuses on the company's ability to earn earnings in the company's operations by utilizing its assets. The purpose of this study is to analyze the influence of the non performing financing factor (NPF), the ratio of operating costs to operating income (BOPO), and financing to deposit ratio (FDR) on profitability in Islamic banking in Indonesia as measured by return on assets. The analytical method used in this study is multiple linear regression. The results of this study indicate that the simultaneous non performing financing (NPF), the ratio of operating costs to operating income (BOPO), and financing to deposit ratio (FDR) affect the return on assets on Islamic banking in Indonesia, while partially non performing financing (NPF) has no effect. The ratio of operating costs to operating income (BOPO) has a negative effect, and financing to deposit ratio (FDR) has a positive effect on profitability in Islamic banking in Indonesia as measured by return on assets. Keywords: Profitability, Non performing financing factor, The ratio of operating costs to operating income, Financing to deposit ratio